The effects of the plyometric sport training model on the development of the vertical jump of volleyball players - Stojanovic, T.; Kostic, R. (Facta Universitatis: Series Physical Education and Sport, 2002)
With the aim to investigate the plyometric training model used for the increase of explosive type strength (the vertical jump), an experimental research was carried out, drawing a sample of 33 volleyball players at the cadet level. Guided by the general principles of plyometric training, individual training plans were devised. In order to evaluate the effect of the sport training on the development of the vertical jump, three variables were applied. For the purposes of this research, two tests for the evaluation of the volleyball vertical jump were validated: the block jump and the spike jump. The experiment was carried out in the second part of the preliminary period, and it lasted for eight weeks, during which, two to three training sessions per week were held. The control group trained using technically tactical contents. The data was processed using univariate and multivariate analyses as well as a covariance analysis. Based on the findings of the research and the discussion, one could unfailingly conclude that the exercise model for the development of the vertical jump that had been used, as the fundamental factor of the experimental group, has contributed to the statistically relevant difference in the increase of the vertical jump in comparison to the control group, which had used technicallytactical contents to develop the vertical jump.